The Correlation Between Students’ Exposure to English Content on TikTok and Their Speaking Confidence - Rifa Azmi Fadhillah; Yeni Rahmawati; Ade Ismail Ramadhan Hamid (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study investigated the correlation between exposure to English-language content on TikTok and the speaking confidence of English as a Foreign Language (EFL) learner. In the digital age, platforms like TikTok offer abundant informal exposure to authentic English input, yet its specific impact on affective factors like speaking confidence remains underexplored. Using a quantitative correlational design, data were collected via a questionnaire from 157 undergraduate students in the English Education Department at Universitas Muhammadiyah Kalimantan Timur. The instruments demonstrated high reliability (Cronbach’s Alpha > 0.91). Data analysis using Spearman’s rho revealed a significant positive correlation between the frequency of watching English TikTok content and self-reported speaking confidence (r = 0.608, p < 0.001). The findings suggest that even passive, informal exposure to English on social media is associated with higher levels of speaking confidence among learners. This study concludes that TikTok can serve as a supplementary informal learning resource that positively influences the affective domain of language learning. It recommends that educators acknowledge and potentially guide students’ use of such platforms to foster a more confident learning environment. Keywords: Digital Media, English as a Foreign Language, Informal Learning, Speaking Confidence, TikTok